Evolutionary conserved gene co-expression drives generation of self-antigen diversity in medullary thymic epithelial cells - Rattay, Kristin; Meyer, Hannah V.; Herrmann, Carl; Brors, Benedikt; Kyewski, Bruno (Journal of autoimmunity, 2016)
Promiscuous expression of a plethora of tissue-restricted antigens (TRAs) in medullary thymic epithelial cells (mTECs) is essential for central tolerance. This promiscuous gene expression (pGE) is characterized by inclusion of a broad range of TRAs and by its mosaic expression patterns, i.e. each antigen is only expressed in 1-3% of mTECs. It is currently unclear to which extent random and/or deterministic mechanisms are involved in the regulation of pGE. In order to address this issue, we deconstructed the transcriptional heterogeneity in mTEC to minor subsets expressing a particular TRA. We identified six delineable co-expression groups in mouse mTECs. These co-expression groups displayed a variable degree of mutual overlap and mapped to different stages of mTEC development. Co-expressed genes showed chromosomal preference and clustered within delimited genomic regions. Moreover, co-expression groups in mice and humans selected by a pair of orthologous genes preferentially co-expressed sets of orthologous genes attesting to the species conservation of pGE between mouse and human. Furthermore, co-expressed genes were enriched for specific transcription factor binding motifs concomitant with up-regulation of the corresponding transcription factors, implicating additional factors in the regulation of pGE besides the Autoimmune Regulator (Aire). Thus promiscuous transcription of self-antigens in mTECs entails a highly coordinated process, which is evolutionary strictly conserved between species.